2014
DOI: 10.1007/s10653-014-9609-4
|View full text |Cite
|
Sign up to set email alerts
|

Dust from Zambian smelters: mineralogy and contaminant bioaccessibility

Abstract: Metal smelting is often responsible for local contamination of environmental compartments. Dust materials escaping from the smelting facilities not only settle in the soil, but can also have direct effects on populations living close to these operations (by ingestion or inhalation). In this particular study, we investigate dusts from Cu-Co metal smelters in the Zambian Copperbelt, using a combination of mineralogical techniques (XRD, SEM/EDS, and TEM/EDS), in order to understand the solid speciation of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The top-down approach would involve the formation of CuS x phases through the breakdown of larger (micrometer-size) particles most likely emitted by the smelter. For example, Lanteigne et al, 36,57 Knight and Henderson 47 and Ettler et al 58 showed that micrometer-size CuS x phases are common in smelter-emitted particulate matter (PM) in the surcial soils of Sudbury, Rouyn-Noranda and Namibia, respectively, however, numerous observations point against this top-down approach:…”
Section: Cus X Phasesmentioning
confidence: 99%
“…The top-down approach would involve the formation of CuS x phases through the breakdown of larger (micrometer-size) particles most likely emitted by the smelter. For example, Lanteigne et al, 36,57 Knight and Henderson 47 and Ettler et al 58 showed that micrometer-size CuS x phases are common in smelter-emitted particulate matter (PM) in the surcial soils of Sudbury, Rouyn-Noranda and Namibia, respectively, however, numerous observations point against this top-down approach:…”
Section: Cus X Phasesmentioning
confidence: 99%
“…However, it is assumed that larger inhaled particles (2.5–10 μm) are cleared from the airways by the mucociliary escalator, swallowed, and transported into the gastrointestinal tract so that only particles <2.5 μm can access the deep lung (e.g., Kastury et al., 2017 ; Meza‐Figueroa et al., 2020 ; Morman & Plumlee, 2013 and references therein). It is also known that the release of contaminants in a simulated lung fluid (SLF) is substantially lower compared to the highly acidic SGF, especially because of the near‐neutral pH of the SLF (see, e.g., Ettler et al., 2014 ; Plumlee & Morman, 2011 ; Thomas et al., 2018 ). For this reason, we decided to perform oral bioaccessibility tests only, which correspond to the “worst‐case scenario.” The bioaccessibility extractions were carried out according to the experimental protocol called SBRC‐G (gastric phase extraction using the Solubility Bioaccessibility Research Consortium assay) adopted by US EPA ( 2007 , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas many bioaccessibility studies have been conducted in developed parts of the world, similar investigations are still relatively rare in the sub‐Saharan Africa, where direct exposure to (contaminated) dust is expected to be significantly higher than in high‐income countries. The high risks of metal(loid) contaminant intake through dust ingestion and inhalation have been demonstrated in pioneering biomonitoring and bioaccessibility studies from the ore mining and processing areas of DR Congo (Banza et al., 2009 ; Cheyns et al., 2014 ), Namibia (Ettler et al., 2019 ; Kříbek et al., 2014 ; Mapani et al., 2010 ; Nejeschlebová et al., 2015 ), Zambia (Ettler et al., 2012 , 2014 , 2020 ; Kříbek et al., 2019 ; Yabe et al., 2018 ) and Uganda (Mwesigye et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[23] In addition, PM 10 collected on different types of filters (quartz fibre filters [24, 25], Teflon filters [26] and cellulose nitrate filters [27]) have been analysed. A key study [3] proposed a novel in vitro simulated epithelial lung fluid that contained high molecular mass proteins, antioxidants and a surfactant, in addition to inorganic components, and so more closely simulated conditions in the real human respiratory system.…”
Section: Introductionmentioning
confidence: 99%